Meningkatkan UMKM Jus Buah Bu Ida dengan Mengoptimumkan Penjualan Menggunakan Metode Simpleks dalam Linear Programming - Ria Agustina; Ruth Sanaya Nainggolan; Suvriadi Panggabean (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2024)
household industry or usually known quantity when UMKM is an arising chance. Rephrase. This happens because there are very few job break. However, some UMKMs still have adversity determining the optimal production abundance broad- based on accessible expedient, so these troop cannot amplify. One of them is Bu Ida fruit juice, which consistently produces fruit juice according to crowd-pleasing orders of average consumer credit. admittedly utilize capital and basic materials enough, Ms. Ida's business is growing day by day. From this research, problems were distinguish and answer live needed, comprehend the employment of linear programming to determine the sales abundance that absence to be optimized to attain maximum earnings from juice sales Ida's fruit. There are 6 (six) juices and 6 (six) ingredients. In this study, a simple method linear programming algorithm is applied to obtain an optimization model to maximize the juice production quantity and obtain optimal profits. The POM-QM Windows application provides fast, accurate and precise calculation results.